2014
DOI: 10.1007/s40299-014-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

A Singapore Case Study of Curriculum Innovation in the Twenty-First Century: Demands, Tensions and Deliberations

Abstract: With the ever-pressing twenty-first century demands, such as the need for new knowledge generation and application, schools today are aware of the necessity to change their structures, processes and practices to be relevant. In Singapore's centralized education system, the Ministry has introduced several decentralization initiatives in the hope of promoting flexibility and innovation within schools. One such initiative is the Integrated Programme (IP). IP schools are expected to redefine existing educational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A study on educational reform in Singapore (Koh et al, 2014) demonstrated the importance of building buy-in of stakeholders for the new curriculum. This involves constant and detailed communication on the changes and providing stakeholders the opportunity to give feedback and comments on proposed changes.…”
Section: Change Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…A study on educational reform in Singapore (Koh et al, 2014) demonstrated the importance of building buy-in of stakeholders for the new curriculum. This involves constant and detailed communication on the changes and providing stakeholders the opportunity to give feedback and comments on proposed changes.…”
Section: Change Managementmentioning
confidence: 99%
“…This involves constant and detailed communication on the changes and providing stakeholders the opportunity to give feedback and comments on proposed changes. Koh et al (2014) also noted the importance of providing autonomy, empowering teachers and giving them a role in the development of modules. The tensions between the new curriculum and institutional directions were resolved by allowing schools to customize the curriculum to the school vision and social, cultural and historical capital.…”
Section: Change Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Under curriculum decentralisation, the locus of CL has recently been transferred from traditional managerial roles to teachers (Koh et al, 2014). Specifically, teachers are empowered with the authority to make both administrative and instructional decisions at the school level, such as planning goals (DeMatthews, 2014), creating a shared vision (Nashashibi & Watters, 2003), building the school climate (Ylimaki & Brunner, 2011), and allocating resources (Lin & Lee, 2013).…”
Section: Teacher Engagement In CLmentioning
confidence: 99%